“migración de las redes de distribución y núcleo de telconet de un esquema plano capa 2 ethernet e ip a un diseño capa 2 802.1q e ip + mpls - Montero Lucio, Carlos (2010)
The technological growth forces Internet Access Providers and data carriers to upgrade their platform in order to satisfy their customers’ expectations. The purpose of this article is to explain the technological change of Telconet S.A. in order to offer new and improved services for layer 2 and 3 networks using MPLS technology and to show the results. During the second semester 2005, Telconet S.A. decided to make fundamental improvements in its distribution and core networks, that is, to improve the main technological infrastructure of the company in order to get a better position in the market and to offer better connectivity solutions and more bandwidth for its users. This implementation had the helping hand of Cisco Systems, world leader in the data networking market. Through an extensive consulting service and the professional and human resources of those who work in Telconet S.A. we designed and implemented a new network with improved capacity and better technological services. Besides numbers and explanations described in this article, the improvement in the quality of TelconetS.A.’s services is the best proof that appropriate decisions were taken and that the offered services satisfy or exceed the requirements of the Ecuadorian corporate market.